A Meta-Analysis of Risk and Protective Factors for Dating Violence Victimization: The Role of Family and Peer Interpersonal Context. (October 2019) - Hébert, Martine; Daspe, Marie-Ève; Lapierre, Andréanne; Godbout, Natacha; Blais, Martin; Fernet, Mylène; Lavoie, Francine
Dating violence (DV) is a widespread social issue that has numerous deleterious repercussions on youths' health. Family and peer risk factors for DV have been widely studied, but with inconsistent methodologies, which complicates global comprehension of the phenomenon. Protective factors, although understudied, constitutes a promising line of research for prevention. To date, there is no comprehensive quantitative review attempting to summarize knowledge on both family and peer factors that increase or decrease the risk for adolescents and emerging adults DV victimization. The current meta-analysis draws on 87 studies with a total sample of 278, 712 adolescents and young adults to examine effect sizes of the association between various family and peer correlates of DV victimization. Results suggest small, significant effect sizes for all the family (various forms of child maltreatment, parental support, and parental monitoring) and peer factors (peer victimization, sexual harassment, affiliation with deviant peers, and supportive/prosocial peers) in the prediction of DV. With few exceptions, forms of DV (psychological, physical, and sexual), gender, and age did not moderate the strength of these associations. In addition, no difference was found between the magnitude of family and peer factors' effect sizes, suggesting that these determinants are equally important in predicting DV. The current results provide future directions for examining relations between risk and protective factors for DV and indicate that both peers and family should be part of the development of efficient prevention options.